Influence of Media Propaganda on the Characters of “Sasa” - DR. MUHAMMAD SOHAIL IQBAL; DR. TAHIRA GHAFOOR (دریافت)
The historical background of the under-study Urdu novel Sasa is a tragedy set in the 21st century. The incident of 11th September 2001, stands as a poignant historical event, reshaping the global political landscape in mere hours. This paper analyses the novel Sasa delving into the far-reaching consequences of the twin tower demolition in New York, particularly resonating across the Muslim world. The repercussions of this calamitous and violent incident extend beyond geographical borders, leaving an indelible mark on nations such as Pakistan, Afghanistan, and Iraq. However, a significant facet of this impact is observed through the lens of Pakistani Muslims residing in the United States and Western countries, who directly grappled with the aftermath of the tragedy. Central to the novel's narrative are characters who embody the multifaceted questions surrounding the motivations behind the tragedy. These questions are intricately woven into the characters' actions and dialogues, unravelling a complex interplay of political, social, and economic issues. As the characters navigate their identities both domestically and abroad, themes of identity, conflict, and harmony emerge as pivotal touchpoints. Within the narrative, Muslim characters hopelessly long for a path of peace amidst the prevailing tide of war, intolerance and animosity propagated by Western and European media. Central to the novel's narrative is a character named Saleem who embodies the multifaceted questions. In quest of his long hunted answer to the question of Love he travels to America, but he had to face hatred instead.  This research employs a qualitative analysis approach, utilizing textual analysis and thematic exploration to unearth the layers of meaning embedded within the characters' experiences and interactions. By contextualizing the characters within a global framework, this study seeks to shed light on the intricate web of human emotions, motivations, and responses triggered by Sasa. Ultimately, the findings contribute to a deeper understanding of the broader sociopolitical repercussions of traumatic events and underline the importance of nuanced narratives that counter prevailing biases and prejudices.